Medium and large sized mammals of the Cerrado domain of Tocantins state, Brazil - Santiago, Wagner Tadeu Vieira; Fonseca, Carlos; Zanzini, Antônio Carlos da Silva; Machado, Felipe Santana; Moura, Aloysio Souza de; Fontes, Marco Aurélio Leite (Revista Agrogeoambiental, 2020)
The Tocantins state is the youngest in Brazil. It is largely occupied by the Cerrado domain, a biodiversity hotspot. Despite estimates of the number of medium and large sized mammals, few studies cover the entire state broadly. In face of the threat that these animals has been suffering from the expansion of agro-pastoral and urban activities, here is presented a high mammal richness that was found on a wide geographic scale in 10 areas, which are distant at least 60 kilometers from each other, from the southern to the northern end of the state, data obtained over 10 years (2001-2011). Two methodologies were used for this study: the Irregular Path Methods and cameras-trap. Forty seven mammal species were recorded, from which 14 species are considered in threat. Records of common species associated with endangered species reinforce the need for further studies to increase knowledge and understanding of the distribution of the mammal community by creating technical and scientific arguments for the development of effective conservation measures and even for the selection of protected areas to wildlife.